The basic logical proposition of Bertrand Russell's pluralistic metaphysics (Damascus University Journal of arts and humanities sciences, 2023)
This research sought to address the reasons for which Russell saw that traditional logic is not suitable for the production of a pluralistic metaphysics, The most important of these reasons was the conception of the traditional logic which says that the Categorical Proposition is the basic Proposition for all other Propositions, given that all other Propositions can be referred to the Categorical Proposition. As for Russell, he refused to accept this conception, in order to emphasize the essentiality of another Proposition, which is the general case, which is the general issue is completely general, It was this matter that allowed him to move without any contradiction, from logic to a sound foundation of a pluralistic metaphysics. This research will attempt to compare the traditional pluralistic metaphysics and its counterpart as it is with Russell, by following the comparative method, in order to clarify the reasons for the existing contradiction between the traditional pluralistic metaphysics and traditional logic, and Russell got rid of this contradiction by adopting new logical conceptions. Keywords: Logical Proposition, Categorical Proposition, Relations, The Fact, Pluralism.
Keywords: Logical Proposition, Categorical Proposition, Relations, The Fact, Pluralism.